Bio-deteriorative Effect on Physico-chemical Properties of Oil of Various Mother Tree Age Classes of Neem (Azadirachta indica A. Juss) Seed during Storage - Kumar, Devendra; Mishra, Dhruv Kumar; Singh, Balbir (Indian Forester, 2007)
Effect of storage period on physico-chemical properties of Neem oil and its affect on seed germination on seeds collected from various age classes were observed. Changes in physicochemical properties of Neem oil lead to change in seed quality during storage like delayed germination, growth and abnormalities in developing seedlings. All age classes showed similar pattern in reduction/increase in physico-chemical properties of oil obtained after storage. Age class IV (>30 years) was found the best for oil production but their seeds lost viability rapidly as compared to others due to faster rate in rancidity of oil inside the cotyledons of seeds. However, no germination was recorded after 65 days of storage at ambient room temperature in all the age classes.